Healthcare middle managers` experiences developing leadership capacity and capability in a public funded learning network - Trude Anita Hartviksen; Berit Mosseng Sjolie; Jessica Aspfors; Lisbeth Uhrenfeldt (BMC, 2018)
Abstract Background Healthcare middle managers (HMMs) have, as the leaders closest to clinical practice, a crucial position in healthcare today. There is broad knowledge about the demands on HMMs' capacity, their situation in general, and the challenges this presents for the improvement of healthcare quality. There is less knowledge about how to facilitate HMMs` capacity and capability with regard to their leadership and how to handle this in a complex context. The purpose of this study was to identify and discuss the facilitation of HMMs' development of capacity and capability for leadership. Method A critical hermeneutic design was chosen. Data were collected through three focus group interviews with Norwegian HMMs who participated in a learning network. A user representative (from among the recipients of public healthcare), involved in the same learning network, participated in all three interviews. A qualitative interpretive approach guided the analysis. Results The results show two main themes: 1. Trusted interaction despite organizational and structural frames and 2. Knowledgeable understanding of a complex context. Conclusion This learning network facilitated HMMs` development of capacity and capability for leadership. The development included a combination of understanding the complex context, knowledge, trust, and confidence. The approaches in the learning network were based on transformative learning, coherence, reflection, discussion, repetition, knowledge sharing, and short lectures. These approaches can be recommended for the facilitation and support of HMMs.